Average nutrient and chlorophyll distributions in the western Mediterranean: RADMED project - María del Carmen García-Martínez; Manuel Vargas-Yáñez; Francina Moya; Rocío Santiago; María Muñoz; Andreas Reul; Teodoro Ramírez; Rosa Balbín (Oceanologia)
Because of its reduced dimensions and its location, surrounded by three continents, the Mediterranean Sea could be especially vulnerable to climate change effects. An increase of the water column stratification could inhibit winter mixing and reduce the frequency and intensity of convection processes which inject nutrients into the photic layer and are responsible for the ventilation of deep waters. In this context, the long-term monitoring of the Mediterranean waters is a basic task. The RADMED project is a monitoring program that covers the waters from the eastern side of the Gibraltar Strait to the Catalan and Balearic Seas. This project was initiated in 2007, merging some previous programs, some of them initiated in 1992. The main objective of this project is to establish average distributions, ranges of variability and long-term trends for physical, and biochemical variables which could be considered as indicative of the environmental state of the sea. The present work analyses nutrient, chlorophyll and oxygen time series from 2007 to 2015 in some cases and from 1992 in other cases. The current analyses show a clear trophic gradient in the RADMED area. Nutrient and chlorophyll concentrations and the intensity of the deep chlorophyll maximum decrease northeastward. The deep chlorophyll maximum depth increases to the northeast. The Balearic and Catalan Seas show a clear seasonal pattern with maximum surface concentrations for nutrients and chlorophyll in winter/spring, associated with winter mixing. On the contrary, the Alboran Sea does not show such a clear seasonal cycle, probably because of the existence of permanent upwelling processes acting along the whole year. The Atlantic Water occupying the upper part of the water column shows a Redfield N:P ratio close to or lower than 16, indicating no phosphorus limitation. Finally, chlorophyll concentrations seem to have increased from 1992 to 2015 in the Alboran Sea, while no long-term changes could be established for the rest of the variables and geographical areas. Keywords: Inorganic nutrients, Chlorophyll, Western Mediterranean, Climatological values, Time series, Climate change